Applicability of a digital health application for cancer patients: a qualitative non-participation analysis - Klara Pfeifer; Mitra Tewes; Stefan Kasper; Jörg Hense; Jan Franco; Martin Schuler; Christoph Schöbel; Gülay Ates (BMC, 2024)
Abstract Background The use of digital health applications (German acronym DiGA) for comprehensive patient care is increasing rapidly. Patients with non-organic insomnia can be prescribed an application to manage insomnia. Due to the high prevalence of insomnia in patients with cancer, we were interested in the effect of it and what barriers need to be overcome for its use. The focus of existing studies on acceptance and benefits prompted us to emphasise the analysis of barriers and thus to formulate possible solutions. Methods To analyse the barriers of use, the study population (patients with self-reported tiredness or sleep disturbance via validated instruments and cancer disease) was divided into 3 groups. In groups 1 (patients who refused to participate in advance) and 2 (patients who refused a prescription), short close-ended questionnaires were used for non-response assessment by treating oncologists. Problem-centred guidelines were used for the telephone interviews with group 3 (patients who did not provide information on DiGA use). Alternatively, group 3 was invited to complete and return the close-ended questionnaire. A quantitative analysis of the non-response reasons was conducted using SPSS in groups 1 and 2, while MAXQDA was used for the qualitative data in group 3. Results Patients refused to participate at several stages of our study. Quantitative data are available for groups 1 and 2. In the largest group 1, 62% of patients refused to participate due to non-subjective sleep disturbance (177 out of 189 patients) during recruitment by treating oncologists, despite high scores on the screening tool. In the small group 2 (11 out of 15), the most common reasons for withdrawal documented by the oncologists were loss of interest and deteriorating health. The problem-centred qualitative interviews with group 3 (17 patients) revealed that some of them used the prescribed DiGA, despite not being included in the main study and being categorized as lost to follow-up. Conclusion Analysis of barriers to DiGA use showed that reducing administrative barriers and providing digital and personal support can increase acceptance of the use of DiGAs among cancer patients. Additionally, screening tools can act as a door opener to further communication regarding DiGAs. Trial registration German Register of Clinical Trials DRKS00034198, registration date: 7/05/24 (retrospectively registered).